Suppression of reactive oxygen species and nitric oxide by asparagus racemosus root extract using in vitro Studies - Visavadiya, N P; Soni, B; Madamwar, D (Cellular and Molecular Biology, 2009)
Recent clinical and experimental data showed the involvement of reactive oxygen species/nitrogen species (ROS/RNS) in many human pathophysiolgocial conditions. Antioxidant activity of the aqueous (ARA) and ethanolic extracts (ARE) of Asparagus racemosus (AR) root were evaluated in a series of in vitro assays including ROS generation in chemicals and biological model systems. The dose-dependant ARA and ARE extracts showed the scavenging activity against DPPH (IC50 = 60.7 and 52.5 µg/ml), nitric oxide (IC50 = 141.9 and 63.4 µg/ml), superoxide (IC50 = 221 and 89.4 µg/ml), hydroxyl (IC50 = 318.7 and 208.8 µg/ml) and ABTS+ (IC50 = 134.5 and 71.9 µg/ml) radicals. The antioxidant capacity of ARA and ARE were assessed for their reducing power using FRAP (Ferric Reducing antioxidant power) and potassium ferricyanide reducing methods as well as free radical scavenging capacity by TEAC (Trolox Equivalent Antioxdaint Capacity) method. ARA and ARE extracts were also found to be effective at suppressing lipid peroxidation induced by Fe2+/ascorbate system in rat liver mitochondrial preparation (IC50 = 511.7 and 309.2 µg/ml, respectively). Further, ARA and ARE root extracts significantly decreased (P < 0.05) copper-mediated human LDL oxidation by prolongation of lag phase time with decline in oxidation rate, maximal yield of conjugated dienes, lipid hydroperoxides and malondialdehyde concentrations. The addition of ARA and ARE root extracts to human serum significantly reduced (P < 0.05) the formation of lipid peroxidation in medium. Trolox, Î±-tocopherol and mannitol were tested similarly to compare their antioxidant activities. In conclusion, antioxidant activity of ARE as compared to ARA extract is more effective which act as hydrogen donors, metal ion chelators, reducing agents, radical scavengers and anti-lipid peroxidative. These effects are attributed to the high amount of lipophilic phenolics content of ARE root extract.